Automatic quantification of retinal photoreceptor integrity to predict persistent disease activity in neovascular age-related macular degeneration using deep learning - Song, Xian; Xu, Qian; Li, Haiming; Fan, Qian; Zheng, Yefeng; Zhang, Qiang; Chu, Chunyan; Zhang, Zhicheng; Yuan, Chenglang; Ning, Munan; Bian, Cheng; Ma, Kai; et al. (Frontiers in Neuroscience, 2022)
Purpose: Using a deep learning-based technique, identify risk factors and create a prediction model for refractory neovascular age-related macular degeneration (nAMD) characterized by persistent disease activity (PDA) in spectral domain optical coherence tomography (SD-OCT) images. Methods: A total of 671 typical B-scans were collected from 186 eyes of 186 patients with nAMD. SD-OCT images were analyzed using a classification convolutional neural network (CNN) and a fully convolutional network (FCN) algorithm to extract six features involved in nAMD, including ellipsoid zone (EZ), external limiting membranes (ELM) , intraretinal fluid (IRF), subretinal fluid (SRF), pigment epithelium detachment (PED), and subretinal hyperreflective material (SHRM). Random forest models were probed to predict one-year disease activity (stable, PDA, and cured) based on the quantitative features computed from automated segmentation, and evaluated with cross-validation. Results: The algorithm to segment six SD-OCT features achieved the mean accuracy of 0.930 (95% CI: 0.916–0.943), Dice coefficients of 0.873 (95% CI: 0.847–0.899), sensitivity of 0.873 (95% CI: 0.844–0.910), specificity of 0.922 (95% CI: 0.905–0.940). The six-metric model including EZ and ELM achieved the optimal performance to predict one-year disease activity, with an area under the receiver operating characteristic (ROC) curve (AUC) of 0.980, accuracy of 0.930, sensitivity of 0.920 and specificity of 0.962. The integrity of EZ and ELM significantly improved the performance of the six-metric model than that of the four-metric model. Conclusion: The prediction model reveals the potential to predict PDA in nAMD eyes. The integrity of EZ and ELM constituted the strongest predictive factor for PDA in nAMD eyes in real-world clinical practice. The results of this study are a significant step toward image-guided prediction of long-term disease activity in the management of nAMD and highlight the importance of automatic identification of photoreceptor layers.